This is easy to do because you can factor
example
6/2=3 because 6=2*3 so 6/2=3/1 times 2/2 or 3
2x^3+17x^2+23x-42 can be factored out to equal
(x-1)(x+6)(2x+7)
so [(x-1)(x+6)(2x+7)]/(2x+7)=[(x-1)(x+6)] times (2x+7)/(2x+7)=(x-1)(x+6)=x^2+5x-6
the answer is (x-1)(x+6) or x^2+5x-6
Answer:
3
Step-by-step explanation:
The slope of the line passing through the points is
m = (y2-y1)/(x2-x1)
= ( 1-2)/(8-5)
= -1/3
The slope that is perpendicular is the negative reciprocal which is
- ( 1/(-1/3)
+ 3/1
The perpendicular slope is 3
<span>x in (-oo:+oo)
((5-9*x)^1)/2 = ((4*x+3)^1)/2 // - ((4*x+3)^1)/2
((5-9*x)^1)/2-(((4*x+3)^1)/2) = 0
(5-9*x)/2-((4*x+3)/2) = 0
(5-9*x)/2+(-1*(4*x+3))/2 = 0
5-1*(4*x+3)-9*x = 0
2-13*x = 0
(2-13*x)/2 = 0
(2-13*x)/2 = 0 // * 2
2-13*x = 0
2-13*x = 0 // - 2
-13*x = -2 // : -13
x = -2/(-13)
x = 2/13
x = 2/13</span>
The first one is 9/25
The second one is 29.44
The last one is 8